Subjective Wellbeing on Parents of Children with Post-Lingual Deafness Disability: Qualitative Study in West Java, Indonesia - ANGGRAINY, DESTALYA; ISKANDARSYAH, AULIA; FITRIANA, EFI; SIREGAR, JUKE (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT These study findings revealed that internal and external aspects determined parents’ subjective wellbeing with children who have post-lingual deafness. Parents with post-lingual deaf children in West Java, Indonesia, were able to cognitively and affectively experience life satisfaction, mainly when their living standards allowed them to satisfy their disabled children’s needs. Affection from family and society also provided supports for parents to interact with their post-lingual deaf children. These findings were expected to serve as references for further studies to improve subjective wellbeing in parents with children with post-lingual deafness. RESUMEN Los hallazgos de este estudio revelaron que los aspectos internos y externos determinaban el bienestar subjetivo de los padres con los niños con sordera poslingual. Los padres con niños sordos post-linguales en Java occidental, Indonesia, pudieron experimentar cognitiva y afectivamente la satisfacción con la vida, principalmente cuando su nivel de vida les permitió satisfacer las necesidades de sus hijos discapacitados. El afecto de la familia y la sociedad también brindó apoyo para que los padres interactuaran con sus hijos sordos post-linguales. Se esperaba que estos hallazgos sirvieran como referencias para estudios adicionales para mejorar el bienestar subjetivo en padres con hijos con sordera poslingual.